2020
DOI: 10.1002/jcc.26193
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and emission properties of 5‐phenyl tris(8‐hydroxyquinolinato) M(III) complexes (M = Al, Ga, In) and correlations with molecular electrostatic potential

Abstract: Substituent effect for a series of 5-phenyl tris(8-hydroxyquinolinato) M(III) complexes (Mq3) of aluminum, gallium, and indium are investigated using density functional theory (DFT) for the ground state properties and the time-dependent version of DFT (TDDFT) for their absorption and emission properties. A comparison between the ground state energy of mer and fac isomers of all the complexes revealed that the mer configuration is always more stable than fac. The substituent effect is significantly reflected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Recently, MESP features have been used to study the ground state as well as the absorption-emission properties of a series of 5-phenyl tris(8-hydroxyquinolinato) M(III) complexes (M = Al, Ga, In). 178 The MESP at the metal center (V M ) and V min corresponding to the (3, +3) CP of the oxygen of phenoxide ring, exhibited excellent correlations with the fluorescence maximum λ F and Stokes shift values. The strong correlations suggested Stokes shift as an experimental quantity to measure the excited state substituent effect while both V min or V M can be used as the corresponding theoretical parameter.…”
Section: Mesp As An Electronic Parametermentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, MESP features have been used to study the ground state as well as the absorption-emission properties of a series of 5-phenyl tris(8-hydroxyquinolinato) M(III) complexes (M = Al, Ga, In). 178 The MESP at the metal center (V M ) and V min corresponding to the (3, +3) CP of the oxygen of phenoxide ring, exhibited excellent correlations with the fluorescence maximum λ F and Stokes shift values. The strong correlations suggested Stokes shift as an experimental quantity to measure the excited state substituent effect while both V min or V M can be used as the corresponding theoretical parameter.…”
Section: Mesp As An Electronic Parametermentioning
confidence: 93%
“…This study also showed that significant change in E 0 occurs when the substituent at para ‐position of 6‐phenyl unit is changed, compared any other positions. Recently, MESP features have been used to study the ground state as well as the absorption‐emission properties of a series of 5‐phenyl tris(8‐hydroxyquinolinato) M(III) complexes (M = Al, Ga, In) 178 . The MESP at the metal center ( V M ) and V min corresponding to the (3, +3) CP of the oxygen of phenoxide ring, exhibited excellent correlations with the fluorescence maximum λ F and Stokes shift values.…”
Section: Mesp As An Electronic Parametermentioning
confidence: 99%
“…The relevance of using MESP for the identification of interactions between polar molecules has been demonstrated many times in literature. [21][22][23][24][25][26][27] However, it should be noticed that some debates are still going on in the literature regarding the relevance of using MESP for interactions of a dispersive nature (in particular benzene dimer, or halide anion and water molecule). 49,50 Gadre and Pundlik [28][29][30][31][32] recommend the use of topological analysis of V(r) to identify the formation of non-covalent complexes while avoiding geometry optimization calculations: in their model (Electrostatic Potential for Intermolecular Complexation, EPIC), the optimal geometry of a complex as well as the interaction energy are determined from the isolated partners.…”
Section: Introductionmentioning
confidence: 99%